Simplified Numerical Model Development for Advanced Design of Lightweight-Concrete Encased Cold-Formed Steel Compressed Elements. (20th May 2022) - Eid, Nathalie; Joó, Attila László
Abstract : The utilization of cold-formed steel (CFS) elements has become more popular recently, due to their cost efficiency and feasibility in construction work. Nevertheless, since such elements are subjected to a variety of complex stability issues, numerous approaches to strengthening have been examined. Namely, CFS members were braced by using lightweight concrete through a previous experimental program. A simplified finite element model was performed consistently with the previous experimental work, to estimate the ultimate load of encased CFS members subjected to compression. The main aim of this research was to overcome the difficulties of modeling the concrete block by substituting the volume element with springs. In addition, a practical equation was proposed to predict the stiffness of springs, and an imperfection amplitude was set to obtain the design capacity of braced CFS compressed elements.